2013
DOI: 10.1038/mt.2013.70
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Modified Synthetic microRNA-205 Inhibits the Growth of Melanoma Cells In Vitro and In Vivo

Abstract: microRNA (miR)-205 is downregulated and acts as a tumor suppressor in human melanoma cells. Previously, for clinical application, we added aromatic benzene-pyridine (BP-type) analogs to the 3'-overhang region of the RNA-strand and changed the sequences of the passenger strand in the miR-143 duplex. Here, we demonstrated the antitumor effect in vitro and in vivo of miR-205 that was also chemically modified by BP and had altered passenger sequence. In in vitro experiments, transfection with the synthetic miR-205… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 30 publications
10
34
0
1
Order By: Relevance
“…Our previous study found miR‐155 to be the most notably upregulated and miR‐205 the most notably downregulated microRNAs in melanoma, as compared with benign melanocytic tumours . Those data are in accordance with several studies reporting the role of miR‐155 as an oncogene and that of miR‐205‐5p as an oncosuppressor in various types of cancer . Taken together, these findings prompted us to further investigate the target genes of miR‐155 and miR‐205.…”
Section: Discussionsupporting
confidence: 89%
“…Our previous study found miR‐155 to be the most notably upregulated and miR‐205 the most notably downregulated microRNAs in melanoma, as compared with benign melanocytic tumours . Those data are in accordance with several studies reporting the role of miR‐155 as an oncogene and that of miR‐205‐5p as an oncosuppressor in various types of cancer . Taken together, these findings prompted us to further investigate the target genes of miR‐155 and miR‐205.…”
Section: Discussionsupporting
confidence: 89%
“…We previously reported that ectopic expression of miR-145 induces apoptosis through the downregulation of c-Myc and socs7 in bladder cancer cells [911]. We thus confirmed this effect by performing assays to evaluate apoptotic cell death in T24 and 253J B-V cells after the transfection of these cells with miR-145 or siR-KLF4.…”
Section: Resultssupporting
confidence: 73%
“…Because the modification shows enhanced nuclease-resistance and also binds a hydrophobic binding pocket of PAZ-domain of Ago2. Among the modified microRNAs, modified miR-205BP (4) significantly inhibited the growth of human melanoma cells [8] (Fig. 10).…”
Section: Anti-melanoma Activity Of Mir-205bpmentioning
confidence: 99%